A jamming‐attack‐defending data forwarding scheme based on channel surfing in wireless sensor networks. Issue 11 (3rd April 2013) - Ghosal, Amrita; Bit, Sipra Das
ABSTRACT: Wireless sensor networks (WSNs) are susceptible to various attacks, and these attacks pose a major threat to the normal functioning of WSNs. Jamming is one such attack, which affects network operations by blocking frequencies. Hence, the need of defending such attack is of utmost importance. This paper proposes three variants of a data forwarding scheme using multi‐level multi‐tier architecture, which employs judicious surfing of a pair of channels to defend jamming attack in WSNs. Variant I defends the attack at the cost of an affordable delay. Improvement of the scheme in minimizing data transmission time is made in variant II. Further improvement in transmission time is made in variant III and is made more realistic by introducing sensing capability at all tiers, thereby increasing network coverage. Simulation is performed to establish each of the successor's variant's improvement over its predecessor. The performance of the scheme in terms of area coverage, packet delivery ratio, and control message overhead is compared with an existing jamming‐defending scheme for infrastructure‐based wireless network. Finally, comparison results establish that although the proposed scheme is equivalent to its infrastructure‐based counterpart in terms of coverage, it provides a more lightweight solution and maintains improved performance in terms of packet delivery ratio. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper proposes a data forwarding scheme with three variants for WSN having multi‐level tier architecture which employs judicious surfing of a pair of channels to defend jamming attack. The performance of the scheme in terms of area coverage, packet delivery ratio and control message overhead is compared with an existing jamming defending scheme for infrastructure‐based wireless network. The comparison results establish that while the proposed scheme is equivalent to its infrastructure‐based counterpart in terms of coverage, it provides more light‐weight solution fulfilling the requirement of infrastructure‐less network like WSN and maintains improved performance in terms of packet delivery ratio. Please use figure 1 for abstract diagram or illustration.